Perception of effectiveness in granting protection measures to women victims of violence, Cartavio, 2019-2023 - Diaz Ruiz, Maria Lucia (2025)
Violence against women is a difficult problem to address that violates their human rights. Law No. 30364 establishes a special process to issue protection measures, precautionary mechanisms aimed at providing an immediate, effective and quality response that puts an end to the violence experienced by women. In light of this, the general objective has been to determine the perception of women victims of violence in the Cartavio Population Center, between 2019 and 2023, in relation to the effectiveness of the protection measures granted. The type of research was basic, qualitative approach, phenomenological design and descriptive scope. High values in frequency and density were obtained in ATLAS.ti software, indicating a significant concern about the lack of immediate attention when going to the Police Station to file a complaint and obtain protection measures, generating distrust in the justice system in general among the interviewees. They also show insecurity regarding the support provided by the protection measures, coupled with the failure to provide a certificate that supports them, perceived as institutional indifference. It is concluded that the interviewees share a perception of ineffectiveness in the face of the meager institutional willingness to provide a comprehensive approach to the situation they are going through.